COMPOSITION DES CONSTITUANTS DES HUILES ESSENTIELLES ET VALEURS NUTRITIVES DU Foeniculum vulgare Mill. (Sciences & Technologie. C, Biotechnologies, 2007)
Foeniculum vulgare  mill.  Plant aromatic,  spontaneous  and widespread  in  Algeria is  used  by  the population for its medicinal virtues.Our samples, coming from the Algerian west, showed that the output of 2.7 in essential oil from the flowering plant is interesting and is in conformity with those obtained by the literature.The index oh iodine and the index of ester determined according to the time and temperature follow an awaited evolution and it is interesting to note a convergence towards a common value for the second index.Thirty components are identified in essential oils of the plant by CPG and CG/SM of which fourteen are not quoted by the literature like pertaining to the plant. The contents of the principal compounds resulting from the primary metabolism and for each part of the plant (seed, stem and roots) are relatively weak and not very interesting on the nutritional level. We however  note  the  absence  of  the  majority  of  the  toxic  components  except  for  the  saponosides  and  the tannins which are in small proportions